Direct Percutaneous Puncture and Embolization of Visceral Pseudoaneurysm: Safety and Clinical Efficacy - Kumar, Sunil K.; Singh, Jagadeesh R.; Kumar, Mahesh; Nagbhushan, K.N.; Reddy, Nageshwar D.; Rao, G.V. (Journal of Clinical Interventional Radiology ISVIR, 2020)
Purpose The aim of the study is to assess the safety and clinical effectiveness of direct percutaneous embolization of visceral artery pseudoaneurysms.Materials and Methods Retrospective analysis of patients who had undergone direct percutaneous embolization of visceral artery pseudoaneurysms between January 2012 and May 2017 was performed. The study included 26 patients with a mean age of 36 years (range 10–71 years). The indications for direct percutaneous embolization included the inability to catheterize endovascularly (n = 24) or prior embolization (n = 2) of the feeding artery. Patient demographics, details of the procedure, complications, and outcomes were evaluated. Patients were followed for a mean of 15 months to assess for recurrence of the pseudoaneurysms on ultrasound.Results Splenic artery (n = 13), gastroduodenal artery (n = 4), right hepatic artery (n = 3), pancreaticoduodenal arteries (n = 3), left gastric artery (n = 2), and left hepatic artery (n = 1) were the embolized arteries. Etiology for pseudoaneurysm were pancreatitis (n = 20), trauma (n = 2), postoperative (n = 2), and few were incidentally detected (n = 2). N-butyl cyanoacrylate (NBCA) with lipiodol was used in 23 (88.4%) patients, coil in one (3.8%), and both coil and NBCA in two patients (7.7%). Embolization of the pseudoaneurysm was successful in all cases. No procedure-related complication was observed. Follow-up showed no recurrence of the pseudoaneurysm. Self-limiting splenic infarct was seen in six patients. Self-limiting abdominal pain was seen in all the patients with embolization with NBCA. One patient developed liver infarct and subsequent liver abscess requiring percutaneous drainage.Conclusion Direct percutaneous embolization is safe and effective in the treatment of visceral artery pseudoaneurysms and should be considered as an alternative in patients with a failed endovascular approach.
Keywords: visceral artery pseudoaneurysm; percutaneous embolization; gastroduodenal artery